Determinants of Ruminant Farmers' Use of Sustainable Production Practices for Climate Change Adaptation and Mitigation in Enugu State, Nigeria - Nwobodo, Cynthia Ebere; Nwokolo, Blessing; Iwuchukwu, Juliana Chinasa; Ohagwu, Violet Amarachukwu; Ozioko, Remigius Ikechukwu (Frontiers in Veterinary Science, 2022)
A sustainable ruminant production system ensures economically viable livestock systems that meet the current and future demands of animal products as well as the environmental safety of current and future generations. The study analyzed the determinants of ruminant farmers’ use of sustainable production practices for climate change adaptation and mitigation in Enugu State, Nigeria. The multistage sampling procedure was used to select 96 ruminant farmers that constituted the sample for the study. A semi-structured interview schedule with open-ended questions was used in data collection. Data were analyzed using multiple regression and Pearson Moment Correlation statistics. Access to veterinary services (t = 2.056; p ≤ 0.05), monthly household income (t = 3.582; p ≤ 0.05) and annual income from ruminant production (t = -2.635; p ≤ 0.011) were socio-economic factors that significantly influenced use of sustainable practices. The adjusted R- square implies that the three factors were able to explain 24% of the variance in the use of sustainable practices. There is a significant positive correlation (r =0.426; p=0.000) between the knowledge level of farmers and their use of sustainable production practices. Schemes for financial inclusion such as payment for ecosystem services can spur farmers to adopt mitigation strategies. Improved climate change knowledge can enhance ruminant farmer’s resilience to the increasing impacts of climate change.